Wittgenstein and philosophy of religion - Arrington, Robert L., 1938-2015; Addis, Mark (Routledge, 2001)
Wittgenstein and Philosophy of Religion is an exciting introduction to the influential and controversial contribution which the later Wittgenstein made to the philosophy of religion.